Hip kinematics during three soccer kicking tasks - Queen, R. M.; Charnock, B. L.; Garrett, Jr., W. E. (2008 Annual Meeting (NACOB) Ann-Arbor, 2008)
Groin injuries have been reported to account for between 5% and 13% of all soccer injuries, however, they result in a substantial loss of time from both practice and competition.(Gilmore, 1998; Wong and Hong, 2005) Groin injuries are most prevalent in sports involving repetitive kicking motions such as soccer, rugby and Australian Rules football, and are most predominant in males.(Gilmore, 1998; Karlsson, et al, 1994) Potential risk factors for groin injuries are thought to be previous strains, direct trauma, overuse and muscular imbalance between the abdominal muscles and adductors. (Gilmore, 1998). Therefore, the purpose of this study was to determine the differences in hip and knee kinematics of the kicking leg during three different kicking tasks in order to determine which kicking task put a player at the greatest risk for a groin injury.